Correlation between neutrophil extracellular traps and macrophages in thrombi of patients with acute ischemic stroke - Mingming Zang; Ruodong Han; Xiuxia Yan (PLoS ONE, 2025)
Objective To investigate the correlation between Neutrophil Extracellular Traps (NETs) content and macrophages in thrombi of acute ischemic stroke (AIS) patients, as well as the differential degradation and clearance capacities of macrophages polarized into distinct functional states. Methods 60 AIS patients treated with endovascular mechanical thrombectomy at Bozhou People’s Hospital were enrolled. Thrombus samples from 30 patients underwent immunohistochemical staining for citrullinated histone 3 (CitH3), CD16, and CD163. CitH3-positive area percentage was quantified to evaluate NETs content. Pearson’s correlation analysis was applied to assess associations between M1(CD16⁺) and M2(CD163⁺) macrophage densities and the CitH3-positive area in thrombus. For the remaining 30 thrombi, co-culture experiments with polarized macrophages were conducted. CitH3 concentrations before and after co-culture were measured via enzyme-linked immunosorbent assay (ELISA), with a blank control group as a reference. Statistical comparisons between groups were performed using Student’s t-tests. Results All 30 thrombi exhibited positive expression of CitH3, CD16, and CD163. CD16+ and CD163+ macrophage densities significantly correlated with CitH3-positive area percentage (r = 0.538 and 0.641, P < 0.05). Co-culture with M1 or M2 macrophages significantly reduced CitH3 concentrations compared to the blank control (P < 0.05). Notably, M1 macrophages demonstrated superior NETs degradation efficacy compared to M2, as evidenced by lower post-co-culture CitH3 levels (P = 0.038). Conclusion NETs are contained in the thrombus of patients with acute ischemic stroke. The numbers of M1 macrophages and M2 macrophages in thrombus are positively correlated with the content of NETs. M1 and M2 macrophages derived from human monocytes have the ability to degrade and clear NETs, and the effect of M1 macrophages in degrading and clearing NETs may be stronger than M2 macrophages.